EFEKTIVITAS KOMUNIKASI APLIKASI ONLINE LINKEDLN SEBAGAI MEDIA INFORMASI LOWONGAN KERJA BAGI ALUMNI UNIVERSITAS RIAU - Siregar, Elida Warni; Rasyid, Anuar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
LinkedIn is an American business and employment-oriented online service that operates via websites and mobile apps. It is mainly used for professional networking, including employers posting their CVs. One of the users who use  LinkedIn app are alumnus of Universitas Riau as a source of job. The theory used in this research is new media theory. This study aims to measure the effectiveness level of the LinkedIn application communication as an online information medium for Riau University alumni.This research is quantitative research, with descriptive approach. The technique of collecting data in this study is using questionnaire to 100 alumnus of Riau University that are determined through random sampling techniques. The data analysis method in this research using descriptive statistical techniques measuring the mean value of each indicator using a formula and with the help of SPSS version 24.The results showed that the LinkedIn application was effective as a medium of information for alumni. This is evidenced by the results of the data collected and measured in six indicators, the measurement of the message recipient indicator obtained a score of 2.73 which is included in the effective scale range, then the results of the measurement of the message content indicator obtained an average score of 2.93 which is also included in the range. effective scale. The results of the measurement of media indicators are in the number 3.02 which is also included in the effective scale range, the format indicator is also in the effective scale range because it obtains an average score of 2.88. The message source indicator gets the final result with an average score of 2.92 which is included in the effective scale range, and the measurement of the timeliness indicator is also in the effective scale range with an average score of 2.71. The average value of the indicator is 2.88 which is included in the effective scale range. Keywords: Communication Efectivity, Information, LinkedIn